Taxonomic status of marine pelagic fishes of India, research priorities and conservation strategies for the sustainability of their fisheries - JAMES, P S B R (The Indian Journal of Animal Sciences, 2010)
The paper briefly reviews the taxonomic status of the marine pelagic fishes of India, lists the research priorities and conservation strategies concerning these fishes. While the taxonomic status of commercially important species/groups of pelagic marine fishes is fairly well determined, the need for such studies on all other lesser known species is pointed out. In the present context of high fishing intensity, minimizing the effects of fishing based on certain biological attributes, would ensure the sustainability of marine pelagic fisheries and the conservation of species.